Analysis of Occupational Accident Risk Control Efforts at PT. XYZ Using the Job Safety Analysis (JSA) and Hazard Identification Risk Assessment (HIRA) Methods: Analisis Risiko Kecelakaan Kerja Pada PT. XYZ Menggunakan Metode Job Safety Analysis (JSA) Dan Hazard Identification Risk Assessment (HIRA) - Rezi Berliana Yasinta; Ahmad, Farhan; Adi Darmawan; Zaki Al Fattah Putra Firmansyah (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
This study aims to analyze the risk of occupational accidents occurring in the production section of PT. XYZ, an automotive manufacturing company. The risk analysis was conducted using the Job Safety Analysis (JSA) and Hazard Identification Risk Assessment (HIRA) methods. The primary data, which consists of occupational accident records from PT. XYZ, is secondary data indicating that in 2023, a total of 61 workplace accidents occurred. Additional data required to validate this research were obtained through literature review. The results of this study include a risk ranking that contains the risk values of occupational accidents obtained through the HIRA method and information on control efforts obtained through the JSA method. The conclusion drawn from the analysis shows that four types of workplace accidents are classified as low-risk, two types as medium-risk, and the control efforts for most types of accidents involve increasing worker awareness and supervision regarding the use of personal protective equipment (PPE) in accordance with standard operating procedures (SOPs), as part of fulfilling occupational health and safety (OHS) aspects in the company.